2005
DOI: 10.1109/tpwrd.2005.848462
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Condition Recognition of Medium-Voltage Vacuum Circuit Breaker Based on Mechanism Dynamic Features Simulation and ANN

Abstract: A new research method is proposed for the medium-voltage (MV) vacuum circuit breaker's (CB's) mechanical condition monitoring, which combines the mechanism dynamic features simulation and mechanical condition recognition algorithm based on artificial neural networks (ANNs). This method includes three steps: First, the relations between eigenvalues and mechanical failures of a vacuum circuit breaker (CB) through simulation instead of measurement are obtained. In this paper, the mechanism dynamic features of a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Compared with other detection methods, such as chassis vibration analysis [3][4][5] and displacement analysis of driving spindle [6][7], CC method performances better on fault detection. Johal [8] introduced the approach to extract the CC features.…”
Section: Introductionmentioning
confidence: 96%
“…Compared with other detection methods, such as chassis vibration analysis [3][4][5] and displacement analysis of driving spindle [6][7], CC method performances better on fault detection. Johal [8] introduced the approach to extract the CC features.…”
Section: Introductionmentioning
confidence: 96%
“…Condition detection and fault diagnosis are the development trend of CB maintenance [9–11]. All kinds of mechanical and electrical signals in CBs are processed by data mining and feature extraction to obtain the features characterized the CB's mechanical state.…”
Section: Introductionmentioning
confidence: 99%
“…However, vibro-acoustic distortions in substation and industrial environment remain the main concern for vibration analysis. Mechanism dynamic features of CB have been used to reveal mechanical failures through different characteristics of the main angle parameter [4]. Furthermore, it has been demonstrated that arcing of CB generates impulsive radio-frequency radiation that can be recorded utilizing digital sampling of the antenna signal.…”
Section: Introductionmentioning
confidence: 99%